Teacher Talk Analysis in the Learning Video ”Descriptive Text’’ from MAS PONPES Darul Qur’an Through Sinclair and Coulthard Model - Halimahtu Saddiah; Ivana Rasikah Azzahra; Susi Eria Agustina; Yoga Marcell Karosekali (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aimed to analyze teacher conversations in the “Descriptive Text” learning video from MAS Ponpes Darul Qur'an using Sinclair and Coulthard's discourse model. With a qualitative descriptive design, data were collected through video observation and transcribed to identify exchanges, movements, and actions in classroom interactions. The results show that the Initiation–Response–Follow-up (IRF) structure dominates classroom discourse, with teachers taking most of the initiative through questions, explanations, and directions, while students generally provide brief and limited responses. Teacher follow-ups are mostly evaluative, using praise and confirmation, which helps maintain motivation but does not expand student cooperation. The discussion highlights that while this teacher-centered approach ensures clarity, structure, and regularity, it also limits opportunities for students to provide longer and more creative responses. The study concludes that teacher talk has a dual role: as a facilitator of learning and as an obstacle when it is too dominant. More varied strategies, such as open-ended questions and in-depth feedback, are recommended to create a more interactive and student-centered classroom environment.